Tumors of giant cells in the forearm - David Alexander Junco Gelpi (Centro Provincial de Información de Ciencias Médicas, 2018)
The case reports of 2 patients assisted in the out-patient Orthopedics Deparment of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba are presented. One had been surgically treated 3 years ago due to a giant cells tumor in the proximal third of the left radius, with a satisfactory clinical course until it began to present volume increase and pain in the distal third of his radio that limited the wrist's flexoextension; the other patient had suffered a traumatism in the distal third of the left forearm and it presented increase of volume between the egdes of the dorsal and ventral sides of the forearm and the wrist. The exeresis to the tumors, with resection in block and external fixation with bank bone implants dedicated to this in the province were carried out. Both patients were discharged without complications and Orthopedics and Oncology follow-up were indicated.